Statistical analysis on Metro Pack Corporation - Castillo, Dominador III; Perez, Amabelle; Segundo, Joana Marie (Diliman, Quezon City College of Engineering, 2001)
Metro-Pack Corporation is one of several companies that engages in the production of packaging materials, specifically carton containers. Major users of the product are food chains and other manufacturing companies that require packaging materials. Like all other companies, Metro-Pack maintains the quality of their product by conducting quality inspections and tests with regard to the reliability of their product. The quality of their product relies heavily on the strength of the packaging materials. With this, the group has decided to conduct a study on the factors that affect the bursting strength of paper boards used in the production system of the company. This parameter was chosen since it is in this area where most of the rejects are recorded. In this statistical analysis, statistical tools were used and a design of experiment was conducted to determine the significance of various factors that affect the bursting strength of paperboards used for the manufacture of boxes. These includes the two factor factorial design, test of hypothesis, Duncan's multiple range test and simple linear regression. The data that was used was gathered from the company being studied. Analysis was conducted to determine the factors that are truly significant to a corresponding output. This was done by following steps in conducting design of experiments (DOE). 1. determining the response variable through problem analysis (bursting strength) 2. generating candidate factors (paper type and the moisture content of the board) 3. determining levels of selected factors from the given data 4. selecting the most suitable experimental design 5. performing the experiment 6. analyzing the drawing conclusions Results have shown that at 0.01 level of significance, only the moisture content affects the bursting strength. The paper type and other interactions do not have significant effect on it. As an effect, the group recommends that the quality control department of the company carry out quality measures that will lead to utmost controlability of the moisture concent of paper boards, in order to standardize the results of the test of bursting strength.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics